Comparison of high-intensity and low-level laser therapy effecton combined sensory index, sensory conduction velocity and distal motoric latency: a study in moderate carpal tunnel syndrome patients - Nelson Sudiyono; Rudy Handoyo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2020)
Carpal tunnel syndrome (CTS) is the most common neuropathy compression syndrome. The effectiveness of low-level laser therapy (LLLT) as one of the conservative therapy for CTS is still debatable. High-intensity laser therapy (HILT) is developed with higher energy and deeper tissue penetration than LLLT. This study aimed to compare the effect of HILT and LLLT on sensory and motoric electrophysiologic parameters in moderate CTS patients. This was an experimental randomized pre and post-test group study. Sixteen patients (fifteen females and one male) with moderate CTS were randomly assigned into two groups. The HILT group was given HILT with analgesic dosage 10 J/cm2 and biostimulation dosage 120 J/cm2. The LLLT group was given LLLT with dosage 6 J/cm2. All treatments were given for ten sessions in 2 weeks. Combined sensory index (CSI), sensory nerve conduction velocity (SNCV), and distal motoric latency (DML) were recorded before and three days after the last treatment. The mean decrease of CSI was more significant in HILT group (-0.37±0.37 ms; p=0.03). There were no significant differences in the mean increase of SNCV (HILT = 3.16±3.15 m/s, LLLT= 2.74±1.42 m/s; p=0.73) and mean decrease in DML between two groups (HILT = - 0.20 ± 0.18 ms , LLLT = - 0.14 ± 0.21 ms; p=0.52). In conclusion, the HILT is more effective than LLLT in improving the CSI values in moderate CTS patients.